2014
DOI: 10.1002/ejoc.201403113
|View full text |Cite
|
Sign up to set email alerts
|

First Microwave‐Assisted Catalytic Wittig Reaction

Abstract: We introduce a novel catalytic Wittig reaction based on an inexpensive and readily available phosphane oxide as a precatalyst. The performance of the reaction under microwave irradiation led to significantly improved yields and reaction rates relative to those obtained under conventional heating. Moreover, herein we enclose the first example of the asymmetric catalytic Wittig reaction based on a chiral phosphane as the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 67 publications
0
20
0
1
Order By: Relevance
“…This was first elaborated for the Wittig reaction using silanes as the reducing agent by O'Brien . Since then, the catalytic Wittig reaction has become a hot topic and found a number of applications . It is worth mentioning that P‐aryl and alkyl phospholanes and phospholenes are the most suitable phosphines in the catalytic cycles due to the easy reducibility of the related ring phosphine oxides .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was first elaborated for the Wittig reaction using silanes as the reducing agent by O'Brien . Since then, the catalytic Wittig reaction has become a hot topic and found a number of applications . It is worth mentioning that P‐aryl and alkyl phospholanes and phospholenes are the most suitable phosphines in the catalytic cycles due to the easy reducibility of the related ring phosphine oxides .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Since then, the catalytic Wittig reaction has become a hot topic and found a number of applications. [11][12][13][14][15][16] It is worth mentioning that P-aryl and alkyl phospholanes and phospholenes are the most suitable phosphines in the catalytic cycles due to the easy reducibility of the related ring phosphine oxides. [7,8] The ring strain is known to significantly aid the deoxygenation of the P=O group.…”
Section: Introductionmentioning
confidence: 99%
“…We have significantly extended the substrate scope of the reaction. Based on our recently reported protocol,23d we chose the reaction of benzaldehyde ( 1a ) and methyl bromoacetate ( 2a ) to form methyl phenyl propenoate ( 3a ) as model reaction (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…In these reactions butylene oxide was used as a base precursor, phenylsilane was the reducing reagent, and the reactions were performed using microwave irradiation (MWI). Subsequently, Werner et al reported the scope and limitations of such microwave-assisted catalytic Wittig reactions using tributylphosphine, phenylsilane and butylene oxide [2324], and reactions with the combination of achiral 30 , trimethoxysilane ((MeO) 3 SiH) and sodium carbonate using conventional heating [25]. …”
Section: Reviewmentioning
confidence: 99%